Phase I/II study of carboplatin plus weekly nab-paclitaxel in patients aged ≥75 years with squamous-cell lung cancer: TORG1322. (August 2020) - Zenke, Yoshitaka; Niho, Seiji; Umemura, Shigeki; Ishihara, Masashi; Seki, Nobuhiko; Nogami, Naoyuki; Hosomi, Yukio; Shimokawa, Tsuneo; Tokito, Takaaki; Goto, Yasushi; Miura, Yosuke; Saito, Haruhiro; et al.
Abstract: Objectives: This phase I/II study assessed the efficacy and safety of combination therapy with carboplatin (CBDCA) and nab-paclitaxel (nab-PTX) in advanced elderly patients (aged ≥75 years) with advanced squamous cell lung cancer (SqCLC). Materials and methods: In this phase I study, the doses of carboplatin at an area under the curve (AUC) of 5 or 6 mg/mL/min on day 1 (levels 1 and 2, respectively) were administered along with weekly nab-PTX (100 mg/m 2 ) on days 1, 8, and 15 every 4 weeks for up to 6 cycles using a modified 3 + 3 design. The primary endpoint for the phase II study was the 6-month progression-free survival (6 m PFS) rate. Results: A total of 46 patients were enrolled in this study. Ten patients were enrolled in the phase I part. At dose level 1, 2/7 patients showed dose-limiting toxicities (DLTs) of grade 3 diarrhea and febrile neutropenia; at dose level 2, 1/3 patient exhibited grade 3 anorexia as a DLT. The recommended dose was determined to be level 2. Efficacy was then evaluated in 39 patients enrolled in a phase II study. The median number of cycles was 4 (range, 1–6), and the median follow-up time was 17.5 months (range, 5.6–28.9 months). The 6 m PFS rate was 59.4% (90% confidence interval [CI], 44.8%–71.4%), and the primary endpoint was met. The median overall survival time was 23.5 months (95% CI, 11.6–35.4), and the median PFS was 6.8 months (95% CI, 5.4–9.1). The response rate was 54%, and the disease control rate was 92%. Sixteen patients (41%) received immune checkpoint inhibitors post-study. Common grade 3 or 4 toxicities were neutropenia (61.5%), anemia (46.2%), thrombocytopenia (17.9%), and febrile neutropenia (15.4%). Conclusion: Combination chemotherapy consisting of CBDCA with weekly nab-PTX had a promising efficacy and acceptable toxicities in elderly patients (aged ≥75 years) with advanced SqCLC.